A biblioteca escolar e a inclusão de alunos com transtorno do espectro autista nas práticas das escolas de ensino fundamental I - Lima, Giovanna Lopes de (Brasil, 2025)
This work presents the results of the study carried out on the inclusion of autistic elementary school students as library users. The research explores the proposals found in the literature on methodologies that can be applied in schools to include autistic children in school activities involved in the library, and in social life. Initially, the work analyzes the legislation related to the right to education and the inclusion of autistic people, with emphasis on Law nº 13.146/2015 and Law nº 12.764/2012. This analysis aims to understand not only the rights of autistic people, but also to understand how they are legally defined. Furthermore, information about the clinical characteristics of autistic people is covered, as the main basis of the DSM – 5, which describes these characteristics in detail. The study also discusses the responsibilities of the family, school and education professionals in relation to autistic people as students and library users, as well as their social inclusion. Through legal and technical texts in the areas of education and health, practices to be adopted by educators and methods to be applied in services are indicated. Regarding the methodology used, considering the objectives of the study, the research procedure was a bibliographic review. Legal and technical texts were collected that supported the theme, object and research problem, as well as analysis of the results. In the analysis of the results, it is observed that, given the characteristics of the autistic student, the level of education and the qualification of the professionals involved, especially the librarian, the most effective and relevant method to encourage reading and promote social inclusion is counting of stories. Although there are other methods and resources available, this was shown to be the most suitable during the research.